2020
DOI: 10.1155/2020/8887782
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Size with Risk of Lymph Node Metastasis in Clear Cell Renal Cell Carcinoma: A Population-Based Study

Abstract: The purpose of this article was to explore the association of tumor size with lymph node metastases (LNM) risk in patients with clear cell renal cell carcinoma (ccRCC). Based on the Surveillance, Epidemiology, and End Result (SEER) database, patients diagnosed with ccRCC from 1988 to 2015 were included in this study. For each patient, personal characteristics, clinicopathological data, and survival outcomes were, respectively, collected. Subsequently, the odds ratios (ORs) and 95% confidence intervals (CIs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…We suggested a whole-body CT scan, even PET/CT is necessary for identifying LNM. Furthermore, we also found a tight correlation between tumor size and the incidence of LNM in RCC, and this correlation has been revealed previously (17,39,40). The web calculator for predicting lymph node metastasis in patients with RCC.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We suggested a whole-body CT scan, even PET/CT is necessary for identifying LNM. Furthermore, we also found a tight correlation between tumor size and the incidence of LNM in RCC, and this correlation has been revealed previously (17,39,40). The web calculator for predicting lymph node metastasis in patients with RCC.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, T stage, M stage, and pathological grade were independent predictors of LNM, Patients with high-level pathological grade, and advanced T and M stages had a higher risk of LNM, probably indicating that tumors were closely related to much more drastic aggressive, which was similar to previous studies (17,18,(36)(37)(38). Meanwhile, Figure 5 also showed that the T stage and M stage were the top two important variables in our five models.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also identi ed the positive relationship of tumor size with the ODF3B expression level (Table 3). According to a study by Zhi et al, an increase in tumor size has been reported in the progression and high risk of lymph node metastases (LNM) in ccRCC (21).…”
Section: Discussionmentioning
confidence: 99%
“…It was in 2019 that there were about 14,000 patients died of RCC in America [ 1 ]. Clear cell renal cell cancer (ccRCC) is the major RCC subtype, whose patients made up for the majority of the diagnosed cases [ 2 ]. ccRCC is a high-risk vascular tumor with no clinical symptoms of manifestation at its early stage, and more than 25-30% of the patients were found along with cancer metastasis as soon as their initial diagnosis of ccRCC, resulted in patients' poor survival prognoses [ 3 ].…”
Section: Introductionmentioning
confidence: 99%